Synthesis of Fibrous Micro-nano Hierarchical Porous Cerium Dioxide Materials by the Impregnation and Thermal Decomposition Method and Its Enhanced Photocatalytic Activity - Zhang, Meng; Chen, Xingwang; Zu, Min; Tang, Yuanzheng; Liu, Chengbao; Li, Wanfei; Chen, Feng (Frontiers in Materials, 2022)
Fibrous micro-nano hierarchical porous cerium dioxide materials were prepared from the oriental paperbush flower stems by impregnation and thermal decomposition method. Field emission scanning electron microscopy (FESEM), powder X-ray diffraction (XRD), transmission electron microscopy (TEM), N2 adsorption-desorption isothermals, temperature-programmed reduction (TPR) and photocatalytic degradation of methylene blue dye were used to characterize the microstructure and photocatalytic property of fibrous micro-nano hierarchical porous cerium dioxide materials. The results proved that the achieved products retained the fibrous morphology similar of oriental paperbush flower stems with the original biotemplate in material completely removed. The average diameter of CeO2 particles on the surface of material is about 9 nm, and the large specific surface area is around 55.6 m2/g. UV-Vis absorption spectra show that the fibrous micro-nano hierarchical porous cerium dioxide materials have high light absorption capacity and can respond to simulate sunlight. Using methylene blue as degradation dye, the effects of initial dye concentration, catalyst concentration, pH value, cycle number and irradiation time on the photocatalytic activity of fibrous micro-nano hierarchical porous cerium dioxide materials were systematically studied. A reasonable photocatalytic mechanism is proposed based on the experimental results and theoretical analysis. This strategy can be extended to synthesize other broad-gap semiconductor oxides with high photocatalytic activity for the photocatalytic degradation of organic dyes under simulated solar irradiation.